The Nature and Extent of Value Change among the Female Youth: Impacts of a Changing Society on the Values and Development of Female Youth (Journal of Advances and Scholarly Researches in Allied Education, 2015)
It has been expressed and properly so excessively that the fate of any country lays on the shoulders of young people of today as they will ultimately turn into the heads of tomorrow. Consequently, anything focused at this gathering of people should be beneficial and aimed at assisting them with satisfying their motivation as would-be pioneers. Administration is a workmanship just as a movement through which the undertakings of men in the general public are coordinated in accordance with the fulfillment of objectives. As young people get readied for influential positions it is relevant to get good guidelines and qualities that will form them into characters prepared to lead for the advancement of the general public. This paper is a talk on how our changing society impacts on youth and virtues.